2018
DOI: 10.1016/j.jaci.2017.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated follicular helper T-cell responses in patients with LRBA deficiency caused by failure of CTLA4-mediated regulation

Abstract: cT cell dysregulation in patients with LRBA deficiency reflects impaired control of T cell differentiation because of profoundly decreased CTLA4 expression on regulatory T cells and probably contributes to autoimmunity in patients with this disease. Serial monitoring of cT cell frequencies is highly useful in gauging the clinical response of LRBA-deficient patients to CTLA4-Ig therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 38 publications
3
65
0
Order By: Relevance
“…However, in contrast to several documented reports regarding the positive correlation of Th17 and IL‐17 with autoimmune disorders, we found that LRBA‐deficient patients have lower peripheral Th17 cells and IL‐17 than in HCs. Our findings were similar to those by Alroqi et al (), who identified that the expression of the Th17‐associated chemokine receptor CCR6 and IL‐17 was markedly decreased in LRBA‐deficient patients, while TFH cells highly expressed the Th1‐associated chemokine receptor CXCR3 and IFN‐γ, compared with HCs. Interestingly, our results showed that LRBA‐deficient patients have higher IL‐17 and IFN‐γ‐double producing cells (Th1‐like Th17 cells) than those in HCs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, in contrast to several documented reports regarding the positive correlation of Th17 and IL‐17 with autoimmune disorders, we found that LRBA‐deficient patients have lower peripheral Th17 cells and IL‐17 than in HCs. Our findings were similar to those by Alroqi et al (), who identified that the expression of the Th17‐associated chemokine receptor CCR6 and IL‐17 was markedly decreased in LRBA‐deficient patients, while TFH cells highly expressed the Th1‐associated chemokine receptor CXCR3 and IFN‐γ, compared with HCs. Interestingly, our results showed that LRBA‐deficient patients have higher IL‐17 and IFN‐γ‐double producing cells (Th1‐like Th17 cells) than those in HCs.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, Charbonnier et al (2015) documented that patients with LRBA deficiency exhibit dysregulated circulating T follicular helper (TFH) cells (a phenotype related to several human autoimmune diseases), due to the profound deficiency of CTLA4 expression by Treg cells (Lo et al, 2015). Recently, Alroqi et al (2017) confirmed previous reports and proposed that TFH dysregulation in LRBA deficiency was not due to an intrinsic abnormality in TFH cells; rather, it reflects the failure of LRBA-deficient Treg cells to control TFH cell differentiation as well as suppression of other effector T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, different murine models have demonstrated that CTLA-4 deletion led to autoimmune manifestations with increased Tfr cells (in both lymph nodes and blood). 162,[174][175][176] Overall, our findings suggest that immunopathogenic stratification of SS patients could be achieved through quantification of blood Tfh-and Tfr-cell subsets. 37,38 In humans, monogenic defects involving CTLA-4 and its intracellular trafficking regulator lead to a primary immunodeficiency characterized by recurrent infections and autoimmunity (characterized by inflammatory bowel disease, autoimmune endocrinopathies, and cytopenias).…”
Section: Tfr Cells For Clinical Precision Immunologymentioning
confidence: 64%
“…15,16,45,51 A possible explanation may be a Tfr-cell expansion as an attempt to restore immune tolerance. [167][168][169][170][171][172][173][174][175] In these patients, as well as in SS patients, treatment with CTLA-4-Ig (Abatacept) was found to partially restore immune homeostasis. 37,38 These mice developed spontaneous GCs, suggesting that expansion of Tfr cells can occur concomitantly with autoimmunity, as far as Tfr cells are defective in their regulation ability.…”
Section: Tfr Cells For Clinical Precision Immunologymentioning
confidence: 99%
“…Primary immune regulatory disorders associated with monogenic defects of genes involved in immune regulatory pathways have been recently identified in patients with multisystem autoimmunity and immunodeficiency. Organ‐specific autoimmunity such as autoimmune cytopenia (AIC), inflammatory bowel disease, autoimmune endocrinopathy, and arthritis are the presenting features in many of these patients, as well as hyperinflammation and nonmalignant lymphoproliferation . Advances in genetic sequencing have supported an expanding list of genetic defects in immune regulatory pathways leading to primary immune regulatory disorders.…”
Section: Introductionmentioning
confidence: 99%